2013
DOI: 10.1016/j.ejvs.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging is More Sensitive than Computed Tomography Angiography for the Detection of Endoleaks after Endovascular Abdominal Aortic Aneurysm Repair: A Systematic Review

Abstract: MRI is more sensitive compared to CTA for the detection of post-EVAR endoleaks, especially for the detection of type II endoleaks. MRI should be considered in patients with continued AAA growth and negative or uncertain findings at CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 29 publications
1
55
0
2
Order By: Relevance
“…The sensitivity of contrast-enhanced ultrasonography for detecting endoleaks was reported to be 81%-98% (24,25). Magnetic resonance imaging was also reported as being more sensitive than CT angiography for the detection of endoleaks (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of contrast-enhanced ultrasonography for detecting endoleaks was reported to be 81%-98% (24,25). Magnetic resonance imaging was also reported as being more sensitive than CT angiography for the detection of endoleaks (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of endoleaks after EVAR is generally reported to be 20-30 %, but endoleaks may be more common than previously believed [11,12]. That is, completion aortography sometimes fails to detect the presence of endoleaks.…”
Section: Discussionmentioning
confidence: 98%
“…One such method, contrast enhanced magnetic resonance imaging (CE-MRI), holds promise for this purpose, as has been shown in a recent meta-analysis, which found that CE-MRI is more sensitive than CTA for the detection of endoleaks, especially for slow flow/type II endoleaks. 6 This is important because type II endoleaks are not always harmless as they may result in adverse outcome after EVAR including rupture. 7,8 Besides standard gadolinium contrast agents, albumin binding contrast agents can be used for MRI examinations aimed at the detection of endoleaks.…”
Section: Introductionmentioning
confidence: 99%